CHARACTERISTICS AND ANALYTICAL METHODS OF MANNITOL: AN UPDATE - SHRIVASTAVA, ALANKAR; SHARMA, SANJAY; KAURAV, MONIKA; SHARMA, ABHISHEK (International Journal of Applied Pharmaceutics, 2021)
Mannitol is an organic compound, a widely distributed natural sugar alcohol in nature. It is found in various plant species and produced by many microorganisms. Mannitol is about 50% as sweet as sucrose, has a low glycaemic index and inert nature, making it suitable to be used in many food products. Mannitol is an osmotic diuretic administering through the iv route and having many clinical usages and is one of the well-known excipients in many different types of formulations. This is also used to increase the dissolution of drugs having solubility problems. Mannitol can be used as a drug and excipient. The goal of this work was to summarize the important physicochemical properties, mechanism of action, production, applications, incompatibilities, polymorphism, and particularly the analytical methodologies published in the last five decades for quantification. Relevant articles related to analytical methods were identified through a search of the English-language literature indexed in Medline, PubMed, ScienceDirect and google scholar from 1970 to till date. The search terms were benign estimation of mannitol, determination of mannitol, methods for determination of mannitol, HPLC and Spectrophotometry method for estimation of mannitol. The methods described in USP, IP, and BP are also described. The presented review also outlines the further scope of research in the field of development of analytical methods.